2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591752
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contribution of the individual alpha frequency (IAF) in an EEG-based study of program comprehension

Abstract: Empirical studies of programming language learnability and usability have thus far depended on indirect measures of human cognitive performance, attempting to capture what is at its essence a purely cognitive exercise through various indicators of comprehension, such as the time spent working out the meaning of code and producing acceptable solutions. We present evidence of the relative contribution of experience and the individual alpha frequency (IAF) to achieving correct performance during program comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…. Some studies found that the increasing cognitive load impacts on developers' performance during the cognitive process, such as, comprehending source code [6,19]. In the case of certain level of cognitive workload jeopardize the developers' comprehension, then the software project probably will be compromised too [14].…”
Section: Research Agenda and Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…. Some studies found that the increasing cognitive load impacts on developers' performance during the cognitive process, such as, comprehending source code [6,19]. In the case of certain level of cognitive workload jeopardize the developers' comprehension, then the software project probably will be compromised too [14].…”
Section: Research Agenda and Challengesmentioning
confidence: 99%
“…Finally, another fact about cognitive load, is that it is affected by the level of experience, and besides that, it can vary across individuals. For instance, Lee 2017 [14] controlled the cognitive load in relation to two experience levels (experienced and no experienced), while in [6] analyzed the cognitive load in relation to 5 categories of experience (from sophomore to seniors one). Therefore, the question is, which are the appropriated categories to analyze the cognitive workload?…”
Section: Research Agenda and Challengesmentioning
confidence: 99%
See 3 more Smart Citations